Effects of a Supraseasonal Drought on the Ecological Attributes of Plagioscion squamosissimus (Heckel, 1840) (Pisces, Sciaenidae) in a Brazilian Reservoir - Antonia E. F. Souza; Jônnata F. Oliveira; Danielle Peretti; Rodrigo Fernandes; Rodrigo S. Costa; José Luis Costa Novaes (The Scientific World Journal)
The aim of this study was to evaluate the effect of a supraseasonal drought on the ecological attributes of Plagioscion squamosissimus. The fish were caught quarterly from February 2010 to November 2014 using gill nets in the reservoir of Santa Cruz, Rio Grande do Norte, Brazil. The abundance of the species was evaluated with the catch per unit effort (CPUE) metric and then correlated with the accumulated rainfall and water volume of the reservoir. The diet of the fish was evaluated using the feeding index (IAi). The proportional similarity index (PSi) was used to evaluate the variation in the niches of the fish. The body condition was inferred through the relative condition factor, and its variation was assessed with ANOVA. A reduction in the abundance of the species that were positively correlated with the reservoir water volume was observed. The diet of the fish comprised shrimp, gastropods, fish, insects, shrimp larvae, and vegetable matter, with shrimp being the major component. PSi showed the occurrence of individual specialization during November 2013 and November 2014. The relative condition factor was not correlated with a reduction in the water volume of the reservoir. The supraseasonal drought did not affect the relative condition factor, diet, and the trophic niche, but it did affect the species abundance.